(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Martynenko S. Formation of the diagnostic competences of future teachers of elementary school. In the article the system of diagnostic skills, which should have future teachers of primary school identified a staged their formation, described the main components forming the diagnostic skills of primary school teachers during their training.